2017
DOI: 10.3892/mmr.2017.7341
|View full text |Cite
|
Sign up to set email alerts
|

Association of a reduction of G-protein coupled receptor 30 expression and the pathogenesis of preeclampsia

Abstract: Preeclampsia is a pregnancy-specific disorder, which is a leading cause of maternal and perinatal mortality and morbidity. A lower increase of estrogen, compared with the increase in progesterone, is associated with pathogenesis of the disease during pregnancy. G-protein-coupled receptor 30 (GPR30) mediates the action of estrogen, however remains to be investigated in preeclampsia. The levels of GPR30 were measured in placentae from uncomplicated pregnancies and pregnancies complicated by preeclampsia using im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
3
15
0
1
Order By: Relevance
“…Other animal models of preeclampsia such as L-N G -Nitroarginine methyl ester (L-Name), induce preeclamptic symptoms through chronic nitric oxide synthase inhibition 8 . However, the dose-dependent hypertension produced by the L-Name treated animals does not model the placental signaling believed to initiate the human disease 28 . The mechanical reduction in placental blood flow in the RUPP makes it ideal for validation of our spectral photoacoustic imaging methods to detect placental ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Other animal models of preeclampsia such as L-N G -Nitroarginine methyl ester (L-Name), induce preeclamptic symptoms through chronic nitric oxide synthase inhibition 8 . However, the dose-dependent hypertension produced by the L-Name treated animals does not model the placental signaling believed to initiate the human disease 28 . The mechanical reduction in placental blood flow in the RUPP makes it ideal for validation of our spectral photoacoustic imaging methods to detect placental ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yin et al observed significantly higher ERα levels within the fetal part of the placenta in severe PE compared with the control group [50]. This finding is especially interesting given the reduced placental levels of another estrogen receptor, GPR30, observed by other authors in both the chorionic villi and decidua of PE patients [51]. It has also been reported that the risk of developing severe PE is associated with polymorphisms in the ESR1 gene [52] which could affect production of the receptor itself.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, a new ER denominated GPR30, which is a G-coupled receptor, has been reported [20]. This new ER participates in the nongenomic actions of E 2 and it has been associated with the estrogen-related tumorogenesis and cardioprotection [21,22], and interestingly, deficiency of GPR30 and 2ME is related to preeclampsia occurrence [23]. Probably, 2ME induces Spon1 expression via GPR30 activation in Ishikawa cells, but this remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%